Injuries and Safe Communities Accreditation: Is there a link?. (June 2016) - Sinelnikov, Sergey; Friedman, Lee S.; Chavez, Emily A.
Highlights: The international Safe Communities (SC) model has shown promise in reducing injuries in community settings. This study is the first attempt to explore injury trends in accredited SC sites from the United States. Using a pre-post intervention-control design, we found lower injury hospitalization rates associated with SC accreditation. Further research is warranted to elucidate the mechanism by which SC accreditation influences injury trends. Abstract: Safe Communities (SC) is a global movement that brings together community stakeholders to collaboratively address injury concerns. SC accreditation is a formal process through which communities are recognized for strengthening local injury prevention capacity. Six million Americans live in 25 SC sites, but no research has been done to understand the model's potential impact on this population. This study explored the temporal relationship between SC accreditation and injury trends in three SC sites from the state of Illinois—Arlington Heights, Itasca, and New Lenox. Hospitalization data, including patient demographics, exposure information, injury outcomes, and economic variables, were obtained from a statewide hospital discharge database for a 12-year period (1999–2011). Joinpoint regression models were fitted to identify any periods of significant change, examine the direction of the injury trend, and to estimate monthly percent changes in injury counts and rates. Poisson random-intercept regression measured the average total change since the official SC accreditation for the three communities combined and compared them to three matched control sites. In joinpoint regression, one of the SC sites showed a 10-year increase in hospitalization cases and rates followed by a two-year decline, and the trend reversal occurred while the community was pursuing the SC accreditation. Injury hospitalizations decreased after accreditation compared to the pre-accreditation period when SC sites were compared to their control counterparts using Poisson modeling. Our findings suggest that the SC model may be a promising approach to reduce injuries. Further research is warranted to replicate these findings in other communities.